Fever in a traveler returning from the Amazon. Do not forget hepatitis A. (2016) - Cunha, Burke A.; Teper, Rina Seerke; Raza, Muhammad
Abstract: Travelers returning from the tropics with fever remain a diagnostic challenge. Fever and chills suggest malaria, but may be present in dengue, chikungunya and influenza, and splenomegaly favors malaria or typhoid fever. In terms of laboratory tests, leukopenia suggests dengue fever, chikungunya fever or influenza. Atypical lymphocytes are present in malaria, dengue fever, chikungunya fever and influenza HAV, but not typhoid fever. Thrombocytopenia is profound in dengue fever, is also present in influenza and malaria. Mildly increased serum transaminases are common in malaria, typhoid fever, dengue fever, chikungunya fever and influenza while very high serum transaminases point to HAV. We present a case of a young woman traveler returning from the Amazon with splenomegaly, leukopenia, atypical lymphocytes, elevated LDH and minimally elevated serum transaminases who was found to have acute hepatitis A infection.